De víctimas a sujetos políticos: mujeres organizadas por la paz - Mendia Azkue, Irantzu (Revista Española de Desarrollo y Cooperación, 2023)
The crucial role women’s organizations play in post-conflict rehabilitation and peacebuilding has become part of the discourse of the majority of international actors, especially after the United Nations Security Council adopted in October 2000 the Resolution 1325 on Women, Peace and Security. This article deals with some of the problematic questions that arise when analysing women’s peace activism, as well as various elements of the peacebuilding experience of organized women in post-war settings.